A - Bima Akmal Fatkhurrozi; Tantina Haryati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the impact of green accounting implementation, carbon emission disclosure, and sustainability report disclosure on firm value among energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The research is grounded in stakeholder, legitimacy, and agency theories, which suggest that companies practicing transparency in environmental and sustainability reporting can positively influence their perceived value. Using quantitative methods and Partial Least Squares (PLS) analysis, this study examines how these disclosures contribute to a firm's market value as perceived by investors, especially in a sector significantly contributing to carbon emissions in Indonesia. The findings reveal that while green accounting practices and sustainability report disclosures positively affect firm value by enhancing transparency and credibility, carbon emission disclosures show inconsistent results in influencing firm value.